Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO290, Tasman Sea, South Pacific Ocean - Andrea Catalina Gebhardt; Emma Hadré; Ruth Supka; Tarik Bozkuyu; Simon Dreutter; Boris Dorschel (PANGAEA, 2023)
Multibeam data were collected during RV Sonne cruise SO290 (2022-04-11 to 2022-05-12). Multibeam sonar system was Kongsberg EM 122 multibeam echosounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs and World Ocean Atlas 13 (https://doi.org/10.7289/v5f769gt), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional blockmedian grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.